Providing a framework for selecting the appropriate method of technology acquisition considering uncertainty in hierarchical group decision-making: Case Study: Interactive television technology - Heidary Dahooie, Jalil; Qorbani, Ali Reza; Daim, Tugrul (Technological forecasting & social change, 2021)
•A new methodology to assist a forecaster to select the appropriate technique using fuzzy sets.•Suitable criteria for selecting a technological forecasting technique.•A challenging case from the aviation technologies with the existence of uncertainty and ambiguity. The technology changes and developments in the world are very rapid and has led many countries and organizations to try to keep up with them through acquisition of technology. Choosing the right method as one of the steps in the technology transfer (TT) process has a significant impact on the successful implementation of technology acquisition (TA). The purpose of this study is to select the most appropriate method of acquiring interactive TV technology for MTN Irancell Telecommunication Company using a combined model of multi-criteria decision-making (MCDM) methods. Therefore, in this research, in the first stage of structuring, the list of criteria and alternatives was determined based on a literature review. Then, in the assessment phase, the fuzzy Delphi technique was used to finalize the list of criteria and alternatives, and then an improved fuzzy group hierarchical best-worst method (fuzzy G-HBWM) was used to determine the criteria weights and evaluate the alternatives by an expert group to form a decision matrix. Finally, in the ranking stage, the alternatives were ranked using fuzzy multi-attribute decision-making (F-MADM) methods including ARAS-F, fuzzy TOPSIS, fuzzy WASPAS, fuzzy VIKOR, fuzzy MABAC, and fuzzy SAW. Then, the Integer Linear Program (ILP) model was used to aggregate the ranking. Based on the results, the main criteria in order of importance are: technology factors, environmental and market factors, organizational factors, and partner or vendor factors. Also, the most important sub-criteria can be considered, respectively, as: the innovative rate in the industry, the degree of strategic importance of technology, the need for access to technology, and the ability to share assets. The final ranking results showed that turnkey contracts, stock ownership, and outsourcing are the top three alternatives in order of priority.